2021
DOI: 10.1002/cam4.4371
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of proton transport inhibitors alone or in combination with cisplatin in triple negative and hormone sensitive breast cancer models

Abstract: Triple negative breast cancers (TNBCs) are very aggressive and have a poor prognosis due to lack of efficacious therapies. The only effective treatment is chemotherapy that however is frequently hindered by the occurrence of drug resistance. We approached this problem in vitro and in vivo on a triple negative and a hormone sensitive breast cancer cell lines: 4T1 and TS/A. A main defense mechanism of tumors is the extrusion of intracellular protons derived from the metabolic shift to glycolysis, and necessary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…In our study, we found that only Lansoprazole was effective in delaying tumor growth and this efficacy was associated with a marked and prolonged reduction in the extracellular tumor acidification, demonstrating the in vivo inhibitory effectiveness of this drug. Recently, another V-ATPase inhibitor, Esomeprazole, demonstrated a remarkable reduced tumor growth and increased survival in the 4T1 TNBC murine model, although tumor pH was not evaluated [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that only Lansoprazole was effective in delaying tumor growth and this efficacy was associated with a marked and prolonged reduction in the extracellular tumor acidification, demonstrating the in vivo inhibitory effectiveness of this drug. Recently, another V-ATPase inhibitor, Esomeprazole, demonstrated a remarkable reduced tumor growth and increased survival in the 4T1 TNBC murine model, although tumor pH was not evaluated [73].…”
Section: Discussionmentioning
confidence: 99%
“…Amiloride, an NHE1 inhibitor, has been shown to provide a moderate cell toxicity in human melanoma cancer cells, although it was ineffective in delaying melanoma tumor growth [74]. In breast cancer cells, only Amiloride derivatives have been investigated, with a modest cell toxicity in both murine and human cell lines, but a single treatment with this Amiloride derivative (EIPA) was less effective in reducing the tumor growth rate than the treatment with cisplatin alone [73,75]. Also in the present study, mice displayed no detectable reduction in tumor growth rate, although a moderate toxicity was observed in cellular experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The MDR problem has even further complexities. Balza et al [ 238 ] , working with two different breast cancer cells, a triple-negative one and a hormone-sensitive one, found that:…”
Section: Discussionmentioning
confidence: 99%